2013
DOI: 10.5539/ijb.v5n4p14
|View full text |Cite
|
Sign up to set email alerts
|

The In vivo Biochemical and Oxidative Changes by Ethanol and Opium Consumption in Syrian Hamsters

Abstract: Daily consumption of opium and alcohol can make people have many health problems, including coronary artery disease diseases (CAD) which has been found to be the most common cause death in opium addicts. The aim of this study was to investigate the effect of simultaneous consumption of alcohol and opium on the lipid profile and oxidative stress in Syrian golden hamsters. Twenty-four male golden Syrian hamsters were randomly divided into four treatment groups (n=6): 1-control (received normal chow), 2-opium (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…The high levels of MDA are known as a positive indicator for lipid peroxidation. Mohammadi et al (19) reported that MDA level significantly increased in opium-treated animals compared to controls (56.52% vs. 30.12 %). The results of the study on Syrian golden hamsters revealed that opium had the capability to stimulate oxidative stress.…”
Section: Malondialdehyde (Mda)mentioning
confidence: 99%
See 1 more Smart Citation
“…The high levels of MDA are known as a positive indicator for lipid peroxidation. Mohammadi et al (19) reported that MDA level significantly increased in opium-treated animals compared to controls (56.52% vs. 30.12 %). The results of the study on Syrian golden hamsters revealed that opium had the capability to stimulate oxidative stress.…”
Section: Malondialdehyde (Mda)mentioning
confidence: 99%
“…In addition, opium raises total cholesterol, Low density lipoprotein-cholesterol (LDL-C), triglyceride (TG) and very low density lipoproteincholesterol (VLDL-C) and reduces high density lipoproteincholesterol (HDL-C), which can act as an atherogenic indicator. It is supposed that reduction of antioxidant activity is in relation to increase of LDL oxidation (19). It was reported that drug abuse is an independent predictive risk factor for improvement of vein thrombosis (14).…”
Section: Malondialdehyde (Mda)mentioning
confidence: 99%
“…Particular attention should be paid to patients with cardiovascular diseases and cardiac risk factors, such as obesity, hypertension, and high cholesterol, as they may be more sensitive to physiological stress, such as increased strain on the heart and the increased cardiac workload induced by alcohol hangovers [1,32,33]. Also, ethanol may provoke oxidative stress [34]. Additionally, it is shown in a systematic review and meta-analysis by Brien et al that moderate intake of alcohol have favourable effects on levels of high density lipoprotein cholesterol, apolipoprotein A1, adiponectin, and fibrinogen which indicates a protective effect of alcohol consumption, particularly associated with a lower risk of coronary heart disease [35].…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Low-density lipoprotein-cholesterol was calculated according to the Friedewaldequation (20)(21)(22).…”
Section: Biochemical Factorsmentioning
confidence: 99%